Application of Clustering Method in Arabic Learning to Improve Speaking Skills for High School Levels - Abidah, Sa’idatul; Febriani, Suci Ramadhanti (Universitas Muhammadiyah Sumatera Barat, 2022)
The main goal of foreign language learning is to make students skilled in using the language both orally and in writing, as well as learning Arabic. However, there are many factors that cause students difficulties in the learning process. One of the contributing factors is the existence of various student characters in the classroom which makes teachers have to be smart in choosing learning methods. One of the appropriate strategies as an effort to overcome these problems is to use the